Corpus-Based Critical Discourse Analysis of Political Themes in Pakistani English Print Media - Isra Mumtaz; Fatima tuz Zahra; Tahir Rasool Bhatti (Corporum)
This study investigates the complex relationship between language, media, and politics through a comprehensive corpus-based critical discourse analysis of political themes in the Pakistani English newspaper Dawnfrom 2018 to 2020. The research uses James Paul Gee’s discourse analysis framework and corpus linguistics tool AntConc to explorehow governance, justice, opposition, and public issues are linguistically constructed and framed. The compiled corpus of 275 articles, encompassing over 200,000 words, was analyzed for collocations, concordance patterns, and thematic structures to uncover how specific linguistic choices reflect and reinforce socio-political ideologies and power relations. Key findings reveal the media’s strategic use of language to shape public narratives, emphasizing governance and accountability while reflecting contentious political dynamics. Gee’s tools, including the Situated Meaning and Big ―D‖ Discourse, were pivotal in identifying how language operates within social contexts to construct broader narratives that resonate with public opinion andinfluence political discourse. This study addresses significant gaps in discourse analysis by integrating qualitative and quantitative methodologies to provide a nuanced understanding of the media’s role in shaping political realities in Pakistan. The research contributes to media studies, political communication, and discourse analysis by offering empirical insights into how language functions as a descriptive and constitutive force. This work lays the foundation for future research to extend these methodologies to other media outlets and linguistic contexts, further illuminating the interplay between language, media, and politics.